Early Tumor Response to Intraarterial or Intravenous Administration of Carboplatin to Treat Naturally Occurring Lower Urinary Tract Carcinoma in Dogs. (21st April 2015) - Culp, W.T.N.; Weisse, C.; Berent, A.C.; Reetz, J.A.; Krick, E.L.; Jackson, D.E.; Kass, P.H.; Clifford, C.A.; Sorenmo, K.U.
<x xml:space="preserve">Abstract</x> Background Survival times and tumor responses associated with malignant neoplasia of the lower urinary tract are poor despite the vast array of current treatments. Therefore, the evaluation of alternative treatments, such as intraarterial administration of chemotherapy (IAC) should be considered. Objective To describe a technique for superselective catheterization for IAC and to evaluate initial tumor response by ultrasonography after both IAC and intravenous administration of chemotherapy (IVC). Animals Client‐owned dogs with lower urinary tract neoplasia treated with either IVC (n = 15) or IAC (n = 11). Methods Retrospective study. An arterial approach via the carotid or femoral artery was utilized to obtain superselective access and administer chemotherapy in the IAC cases. Medical record review was performed, data were recorded, and recorded variables were evaluated statistically. Results Intraarterial chemotherapy was successfully administered in all cases. There was a significantly greater decrease in longest unidimensional measurement in the IAC group as compared to the IVC group (P = .013). The IAC group was also significantly more likely to have a tumor response as assessed by modified RECIST guidelines (P = .049). Dogs in the IAC group were significantly less likely to develop anemia (P = .001), lethargy (P = .010) and anorexia (P = .024). Conclusion and Clinical Importance This study demonstrated the feasibility and efficacy of performing IAC for lower urinary tract neoplasia. Further investigation is necessary as the follow‐up time was short and the impact on long‐term outcome and survival was not determined.